2023
DOI: 10.1080/15592324.2023.2292844
|View full text |Cite
|
Sign up to set email alerts
|

Expression identification of three OsWRKY genes in response to abiotic stress and hormone treatments in rice

Jiangdi Li,
Yating Chen,
Rui Zhang
et al.

Abstract: WRKY transcription factors are critical for plant growth, development, and adaptation to stress. This paper focuses on the expression characteristic to abiotic stress and phytohormones of OsWRKY24 , OsWRKY53 , and OsWRKY70 . Three OsWRKY TFs contained two conserved domains and there were multiple cis -elements in response to adversity stress and hormone signaling in their promoters. Real-time PCR analysis revealed their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…In oil palm, EgWRKY59 and EgWRKY65 contribute to similar regulatory mechanisms involving ABA-, SA-, and ROS-mediated signaling pathways during an exposure to drought or other abiotic stresses; these two genes may be useful for enhancing the abiotic stress tolerance of plants. A recent study showed that OsWRKY24 and OsWRKY70 expression levels are upregulated by low temperatures, SA, and MeJA but are downregulated by ABA [ 50 ]. In Dendrobium officinale seedlings, the expression levels of nine DoWRKY genes are significantly affected by cold and MeJA treatments, suggestive of their contributions to stress tolerance [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In oil palm, EgWRKY59 and EgWRKY65 contribute to similar regulatory mechanisms involving ABA-, SA-, and ROS-mediated signaling pathways during an exposure to drought or other abiotic stresses; these two genes may be useful for enhancing the abiotic stress tolerance of plants. A recent study showed that OsWRKY24 and OsWRKY70 expression levels are upregulated by low temperatures, SA, and MeJA but are downregulated by ABA [ 50 ]. In Dendrobium officinale seedlings, the expression levels of nine DoWRKY genes are significantly affected by cold and MeJA treatments, suggestive of their contributions to stress tolerance [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 90 Sudan grass plants with the same growth rate were selected for each hormone treatment and divided into 3 replicates. Next, 5 Sudan grass plants were taken as samples at 0, 1, 3, 6, 12, and 24 h after treatment with 150 µM ABA [56], 100 µM JA [57], and 2 µM BRs [30], wrapped in aluminum foil, frozen in liquid nitrogen, and stored at −80 • C.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…This viral hijacking of AtWRKY20 spatiotemporally redeployed plant chemical immunity within the leaf [9]. OsWRKY53 was induced by abscisic acid (ABA), jasmonate (JA), salt, drought, darkness, and low temperatures but inhibited by gibberellic acid (GA) and salicylic acid (SA) [10]. The WRKY-TFs in various woody plants were widely involved in responses to biotic and abiotic stresses, as well as in plant growth and development [11].…”
Section: Introductionmentioning
confidence: 99%